The Relationship Between Iron (Fe) Intake and Stunting Incidence in Toddlers Aged 24-59 Months in the Nipah Health Center Work Area - Zakiyyah, Luthfi; Cholidah, Rifana; Amalia, Emmy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
A worldwide issue that has not been adequately addressed is stunting. One of the many causes of stunting is inadequate nutrition. There are two types of nutrients: macronutrients and micronutrients. Iron is one of the micronutrients that the body actually needs. Lack of iron consumption is one of the risk factors for stunting, according to a number of earlier research. The aim of this study was to ascertain the correlation between the occurrence of stunting in toddlers aged 24 to 59 months in the Nipah Health Center work area and iron (Fe) intake. This study employs a case control methodology and combines quantitative and analytical observational methods. Ultimately, we discovered that 30 individuals, or 78.95% of the 38 research participants, had iron intakes below 77%. The statistical test of iron consumption and stunting incidence showed that p = 0.042. This indicates that the incidence of stunting and iron intake are related.